Macrophages transfer antigens to dendritic cells by releasing exosomes containing dead‐cell‐associated antigens partially through a ceramide‐dependent pathway to enhance CD4+ T‐cell responses. Issue 2 (30th July 2016) - Xu, Yingping; Liu, Yi; Yang, Chunqing; Kang, Li; Wang, Meixiang; Hu, Jingxia; He, Hao; Song, Wengang; Tang, Hua
Summary: Defects in rapid clearance of apoptotic cells lead to an accumulation of dead cells (late apoptotic or secondary necrotic cells), which results in an aberrant immune response. However, little is known about whether and how macrophages (M φ s) cooperate with dendritic cells (DCs) in the presentation of dead‐cell‐associated antigens in this process. By transferring high numbers of dead cells to mimic a failure of apoptotic cell clearance in vivo, we found that M φ s and neutrophils were the predominant phagocytes in the uptake of dead cells in the spleen. Moreover, both M φ s and DCs were required for an optimal CD4 + T‐cell response triggered by dead‐cell‐associated antigens. Importantly, although M φ s alone had a poor capacity for antigen presentation, they could transfer phagocytosed antigens to DCs for potent antigen presentation to enhance T‐cell responses. Finally, we found that exosomes released from M φ s acted as a transmitter to convey antigens to DCs partially in a ceramide‐dependent manner, since treatment with the neutral sphingomyelinase inhibitor GW4869 and spiroepoxide resulted in a significant reduction of T‐cell proliferation in vitro and in vivo . These findings point to a novel pathway of cross‐talk between M φ s and DCs, which will be helpful to explain possible mechanisms for autoimmune diseases characterized by increased rates of apoptosis. Abstract : Macrophages (M φ s) were the relative predominant phagocytes engulfing dead cells in the spleen, and transferred antigens to dendritic cells (DCs) by releasing exosomes containing dead‐cell‐associated antigens partially through a ceramide‐dependent pathway to enhance a CD4 + T‐cell response. These findings point to a novel pathway of cross‐talk between M φ s and DCs, which will be helpful to explain possible mechanisms for autoimmune diseases characterized by increased rates of apoptosis.